In the Name of Dark Web Justice: A Crime Script Analysis of Hacking Services and the Underground Justice System. (May 2023) - Choi, Kyung-Shick; Lee, Claire Seungeun
The Dark Web serves as a key venue for peddling illegal goods and services, from stolen possessions and drugs to illicit activities. The concurrent increase in Tor network usage and the development of cryptocurrency has led to the creation of major black market sites. One of the most popular illicit services offered on the Dark Web is hacking, which includes website/social media account hacking, Denial-of-service attacks, and custom malware. At the same time, the Dark Web community has formed its own justice system leveraging the layer of anonymity that exists between underground community users and the cybercrime ecosystem. Existing studies predominantly focus on the major drug market operating on the Dark Web, firearm sales, sexual exploitation, and money laundering. To address the gaps in the current research as well as the relative nascency of an underground justice system to monitor hacking services on the Dark Web, this study attempts to broadly capture the dynamic nature of hacking services, which requires continuous research to identify new trends and develop effective responses. The study aims to examine the characteristics and the operations of the hacking service market and the underground justice system on the Dark Web via an in-depth examination of Dark Web forums with a crime script analysis vis-à-vis thematic analysis. The study defines the crime script as that which includes pretrial, mid-trial, finalization, and exit stages. This research sheds light on Dark Web justice courts' procedures and the courts' implications for shaping the future of the Dark Web.